Congratulations - Campbell, Hamish; Petrey, Allen (New Zealand Science Review, 2020)
Public science policies in Aotearoa New Zealand present an expectation to researchers and educators that their practice will engage with mātauranga Māori.The primary objectives of Science Review are to inform and stimulate. It gives us great pleasure to do just this by giving voice to those who see the enormous potential and significance of mātauranga Māori.The two part issue of Mātauranga and Science in Practice draws together the experiences of Māori, Pākehā and tauiwi scientists, researchers and educators. The issues present a variety of cases that span institutions, disciplines and domains. The collective experience forms a resource that helps us all to better understand how this work can advance Aotearoa NZ’s public knowledge ecosystem.More than 100 people have contributed to this work. The Association of Scientists congratulates all who have contributed to both parts of the special issue and acknowledges the superb effort of guest editors Drs Ocean Mercier and Ann-Marie Jackson especially in the present troubling times of the COVID-19 pandemic.Mātauranga and Science in Practice is a tribute were we, in New Zealand have got thus far in this endeavour. Hamish Campbell and Allen Petrey for NZAS Council